Faktor Penyebab dan Sanksi Tindak Pidana Penipuan Kepemilikan Kendaraan Bermotor Secara Melawan Hukum - Elvi Zahara Lubis (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2017)
One form of crime that increasingly has a certain modus operandi is a crime of motor vehicle fraud unlawfully. Fraud is a crime that belongs to a class devoted to property rights and other rights arising from rights. As formulated in Article 378 of the Criminal Code, fraud means deeds with the intent to benefit themselves or others unlawfully by using false names, false dignity, deceit or lies that may cause others to easily surrender their goods, money or wealth. Factors causing the crime of motor vehicle ownership fraud unlawfully are caused by four factors namely economic factor, desire factor, opportunity factor and the weak factor of faith. Sanctions against perpetrators of criminal fraud of motor vehicle ownership by unlawful means in the form of criminal punishment of imprisonment to perpetrators for 4 years. Such sanctions may be applied if the perpetrator has been proven to commit a criminal act of fraudulent vehicle ownership in a manner which is against the law.